Analisis Metode Tilawati dalam Pembelajaran Baca Tulis Al Qur’an di SD Al Madina Wonosobo - Andri Sungkowo (JIP Jurnal Ilmiah PGMI, 2020)
This study aims to determine the ability of Al Madina Elementary School students to read Al Qur'an before using the Tilawati method, the application of the tilawati method in Al Madina Elementary School and the resulting impact in applying the Tilawati Method in Al Madina Wonosobo Elementary School. The research method used was to use descriptive qualitative methods, interviews and observations. The results of this study are Al Madina Elementary School students before using tilawati method, they have mastered the material, but the ability of each student is not the same and less evenly distributed, the application of tilawati method in Al Madina Elementary School uses a classical and individual approach with three techniques, namely; the technique of one teacher reading students listening, the technique of two teachers reading students imitating, and the technique of three teachers and students reading together, the impact produced in applying this study method all students get the same learning that has an impact on the equal ability of each student in reading the Qur'an with the beat.